THE MEANING OF IRREGULAR PLURALS BETWEEN QUR’ANIC USAGE AND LINGUISTIC USAGE - Mohammed, sardar; Ezzat, Azza (Humanities Journal of University of Zakho, 2026)
The study sheds light on the issue of how the Qur’an’s use of plural forms differs from the commonly known linguistic usage, and highlights the importance of the morphological level in linguistic studies. Any change in morphological structure leads to a change in meaning, and any addition to the morphological structure is an addition to the intended meaning. The Qur’an, therefore, chooses its words with utmost precision and in a rhetorical and expressive manner that has left the greatest masters of Arabic language unable to rival or reproduce it despite their eloquence and linguistic capabilities. Through its styles, shifts, and performance, the Qur’an has elevated the status of the Arabic language, developed it, and raised it to the highest level. Furthermore, the Qur’an selects the most precise form from among a range of forms in a way that suits the context and harmonizes with the surrounding words. Every plural form carries its own specific functional meaning in such a way that no other form can take its place and fully perform its function. For instance, the irregular plural is semantically associated by many with both paucity and multitude, and it may serve that purpose in certain Qur’anic verses. However, many other plural forms cannot be reduced simply to the meanings of paucity or multitude, as in al-aʿyun vs. al-ʿuyūn (“the eyes/ water springs”), al-kuffār vs. al-kafara (“the disbelievers”), al-abrār vs. al-barrara (“the righteous ones/ the righteous angels”), ḥamīr vs. ḥumur (“donkeys”), or when regular plurals are paired with irregular ones, such as al-jāriyāt vs. al-jawārī (“the sailing ships”), al-rāsiyāt vs. al-rawāsī (“the firmly set things/mountains”), and al-khabīthāt vs. al-khabāʾith (“the evil ones”), etc. In this study, we shall do our best to present several examples to illustrate how the Qur’an’s usage diverges from common linguistic usage.